Pengaruh Indeks Pembangunan Manusia (IPM), Angkatan Kerja, dan Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Tana Toraja - Rudo Tanyara Sumbung; Ita Pingkan F. Rorong; Irawaty Masloman (PT. Hasba Edukasi Mandiri, 2025)
Tana Toraja Regency is one of the areas in South Sulawesi province that still faces poverty problems. Tana Toraja is a district whose poverty level is seventh out of a total of 24 districts/cities in South Sulawesi. This research aims to analyze the impact of HDI, AK, and P on poverty levels using time series data sourced from the Central Statistics Agency of Tana Toraja and South Sulawesi. The analysis was carried out using multiple linear regression with the Ordinary Least Square (OLS) method via Eviews 12 software. The results showed that HDI had a negative and insignificant relationship with poverty levels, which means that improving people's quality of life can reduce poverty levels., Labor Force showed a relationship positive and significant, indicating that increasing the number of the workforce has a direct impact on reducing poverty. Meanwhile, Unemployment has a positive and significant relationship, indicating that high levels of unemployment contribute to increasing poverty. Overall, these three variables together have a significant relationship to the level of poverty in Tana Toraja, underscoring the need for integrated policies in poverty alleviation efforts in this area.